Wybrane problemy metodyczne identyfikacji i opisu struktur organizacyjnych przedsiębiorstw - Lichtarski, Janusz Marek (Selected methodical problems of the identification and description of organizational structures of enterprises, 2006)
In the present study the author focuses on the methodical problems of identification of organizational structures of a company. Many different problems were identified during defining the structure of organization, choosing and measuring structural dimensions and gathering empirical information. The goal of the study is to evoke the discussion dedicated to methodical aspects of diagnosis of organizational reality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 71-85